Rational drug design, synthesis and biological evaluation of dihydrofolate reductase inhibitors as antituberculosis agents - Tawari, Nilesh R.; Bag, Seema; Raju, Archana; Lele, Arundhati C.; Bairwa, Ranjeet; Ray, Mukti Kanta; Rajan, M. G. R.; Nawale, Laxman U.; Sarkar, Dhiman; Degani, Mariam S. (Future Medicinal Chemistry, 2015)
Background: A series of 2,4-diamino-s-triazines was designed, with potential for activity against Mycobacterium tuberculosis (Mtb) dihydrofolate reductase enzyme, on the basis of virtual screening results and structure-based drug design. Results: The compounds were evaluated against Mtb (H(37)Rv) and their cytotoxicity was assessed using VERO cell lines. Of particular note, two compounds were found to have the most promising antituberculosis activity (6b minimum inhibitory concentration: 1.76 mu M and 6i minimum inhibitory concentration: 1.57 mu M) along with low cytotoxicity (CC50 : > 300 mu M). The enzyme assay results of these two indicated significant inhibition of Mtb dihydrofolate reductase along with selectivity. Selected derivatives were tested against dormant tubercle bacilli in vivo and ex vivo indicating potential inhibition. Conclusion: This study provides promising antituberculosis dihydrofolate reductase inhibitors that can act as potential leads for further development.

Rational design of coumarin derivatives as antituberculosis agents - Mali, Hemlata M.; Sabale, Sandip S.; Degani, Mariam S.; Borkute, Rachana; Choudhari, Amit S.; Sarkar, Dhiman; Krishna, Vagolu Siva; Sriram, Dharmarajan (Future Medicinal Chemistry, 2018)
A series of coumarin derivatives was designed as potential antituberculosis agents. Results: The compounds were screened against active and dormant Mycobacterium tuberculosis (Mtb). Compounds 3k and 3n were found to have the most promising activity against replicating MtbH37Rv exhibiting minimum inhibitory concentration of 4.63 and 9.75 mu M respectively. The compounds were also effective against dormant MtbH37Rv exhibiting more potency than the standard drugs, isoniazid and rifampicin. The compounds were found to be non-cytotoxic against human cell lines. Conclusion: This study provides promising antituberculosis agents that are effective against replicating as well as dormant Mtb and can thus act as potential leads for further development.